1994
DOI: 10.1037/1064-1297.2.3.269
|View full text |Cite
|
Sign up to set email alerts
|

Memory accessibility and association of alcohol use and its positive outcomes.

Abstract: Theoretical predictions involving memory associations between alcohol use and its positive outcomes were examined. In 2 preliminary studies, the availability from memory of outcomes from drinking was investigated. In subsequent studies, a measurement paradigm was used that decreased the accessibility of the association between drinking behavior and positive outcomes so that individual differences in drinking frequency might predict the accessibility of memory responses. In a final study, this paradigm was refi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
203
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(217 citation statements)
references
References 38 publications
13
203
0
1
Order By: Relevance
“…Echoing theories of implicit social cognition (e.g., Greenwald and Banaji, 1995), an assumption of the present study is that the connections between social interactions and drinking may result in associations in memory between alcohol and social interaction; that is, associations about alcohol may be automatically activated by being in or thinking about certain social contexts. Preliminary evidence suggests this activation occurs in situations where alcohol is present (e.g., Stacy et al, 1994), and it may also occur in contexts without alcohol. Dating contexts are among those social contexts in which automatic alcoholrelated associations might be likely to be activated because of the strong links among alcohol and romance and sex (e.g., Crowe and George, 1989;George and Stoner, 2000).…”
Section: Alcohol and Social Interaction/datingmentioning
confidence: 99%
See 1 more Smart Citation
“…Echoing theories of implicit social cognition (e.g., Greenwald and Banaji, 1995), an assumption of the present study is that the connections between social interactions and drinking may result in associations in memory between alcohol and social interaction; that is, associations about alcohol may be automatically activated by being in or thinking about certain social contexts. Preliminary evidence suggests this activation occurs in situations where alcohol is present (e.g., Stacy et al, 1994), and it may also occur in contexts without alcohol. Dating contexts are among those social contexts in which automatic alcoholrelated associations might be likely to be activated because of the strong links among alcohol and romance and sex (e.g., Crowe and George, 1989;George and Stoner, 2000).…”
Section: Alcohol and Social Interaction/datingmentioning
confidence: 99%
“…Initial research with explicit measures of alcohol-related associations suggests that positive outcome expectancies are activated in alcohol-related contexts (Wall et al, 2000(Wall et al, , 2001, but only one study has been conducted with an implicit measure (Stacy et al, 1994). Stacy et al (1994) found that, compared with participants who read a vignette in which alcohol was absent, participants who read a vignette in which alcohol was present were more likely to endorse alcohol-related behaviors in an outcome association task (i.e., writing the fi rst behavior that comes to mind after seeing an outcome prime, such as "feeling more relaxed"). Additional research is necessary to understand the role of context in automatic alcohol associations, especially environments in which alcohol is present or likely to be present.…”
mentioning
confidence: 99%
“…In basic social psychology, intentions are thought to mediate the relation between attitude and behavior (Ajzen & Fish-bein, 1980). In cognitive psychology, attentional processes are thought to intervene between stimulus and behavior (Stacy, Leigh, & Weingardt, 1994). In industrial psychology, work environment leads to changes in the intervening variable of job perception, which in turn affects behavioral outcomes (James & Brett, 1984 …”
Section: Introductionmentioning
confidence: 99%
“…Many of the analyzed articles evaluated the validity of the methods of IAC assessment and found that: the IAT, the Extrinsic Affective Simon Task (EAST;De Houwer, 2003), the Affect Misattribution Procedure (AMP; Payne, Cheng, Govorun & Stewart, 2005), the Affective Priming Paradigm (APP; Fazio et al, 1986), and the Word Association Test (Stacy, Leigh & Weingardt, 1994) were valid methods to assess IAC (Gray, LaPlante, Bannon, Ambady & Shaffer, 2011;Houben, Rothermund & Wiers, 2009;Lindgren, Westgate, Kilmer, Kaysen & Teachman, 2012;Lindgren, Hendershot, Neighbors, Blayney & Otto, 2011;Ostafin & Palfai, 2006;Payne, Govorun & Arbuckle, 2008).…”
Section: Topic 1: Methods Of Iac Assessmentmentioning
confidence: 99%